Scattered Field Calculation From Microstrip Arrays Using the Combination of Discrete Bodies of Revolution and Domain Decomposition Methods - Hossein Mohammadzadeh; Abolghasem Zeidaabadi Nezhad; Zaker Hossein Firouzeh (IEEE Access, 2023)
This paper analyzes electromagnetic scattering from a microstrip array with a homogeneous dielectric substrate in two symmetry cases. In the first case, the entire structure has discrete rotational symmetry, and the discrete bodies of revolution method is employed for a comprehensive analysis. In the second case, the ground and substrate have discrete rotational symmetry, whereas the patches and feeding lines do not. Therefore, the discrete bodies of revolution method is used to analyze the ground and substrate, the traditional moment method is applied to the patches and feeding lines connected to them, and the domain decomposition method combines the results obtained from these two solutions. As a result, the discrete bodies of revolution method is applied only to one sector of the microstrip array, which reduces the memory requirements and computational time in comparison with the traditional moment method. Consequently, for a structure with $N_{s}$ symmetric sectors and the total number of unknowns $N$ , the memory requirements and simulation time are reduced by factors of $N_{s}^{2}$ and $N_{s}^{3}$ , respectively, in comparison to the traditional moment method. Finally, numerical results are presented to validate the accuracy and efficiency of the proposed method. The results are compared with those obtained from commercial FEKO software and the traditional moment method to show how the proposed method reduces computation time and memory requirements.